Influência de adições de grafite, óxido de grafite e grafite-like em argamassa de cimento Portland : durabilidade, propriedades mecânicas e resistividade elétrica - Mendonça, Michella Graziela Santos (2019)
The incorporation of carbon nanotubes, graphenes and graphene oxides in cement matrices has been extensively studied due to their ability to add conductive properties and simultaneously perform reinforcing function. However, the high cost of those materials for large scale applications has recently triggered the search for low cost materials with similar properties. In such context, the first study of this thesis investigated the behavior of the electrical resistivity, mechanical strength and durability properties for graphite, graphite oxide and graphite-like mortars, low cost alternative materials with similar properties. The results showed that the addition of graphite demonstrated progressive impairment of the compressive strength and revealed no significant variation in flexural strength. Elseways, the addition of graphite oxide did not compromise the compressive strength and exhibited flexural strength gains. The electrical resistivity of mortars was found in the following ascending order: graphitelike, graphite and graphite oxide. In another context, the use of carbon fiber in recent years has increased substantially, resulting in a higher volume of carbon fiber waste resulting from losses. In this follow-up, the second study of this thesis investigated the use of carbon fiber waste in cement mortars and coir pith particles, as well as the effect of the use of milling in the production process. Physical, mechanical and durability properties were evaluated. The use of the milling process resulted in a 87% gain in compressive strength. The addition of carbon fibers resulted in an up to 192% gain in flexural strength. Durability results showed stability in the mechanical flexural property over time for the mortars with carbon fiber.